Wars, Traumas, and Identities in the Serbian Novel 1991–2021 (II) - Brajović, Tihomir D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The second part of the paper deals with the testimonial-representative paradigm as a choice based on the personal expression of unique experiences of traumatic events as a frame for contemporary concrete understanding and a kind of cathartic solution to identity contradictions. The outcome shows that both paradigms could also be productive in articulating adequate identity politics and/or principle understandings of identity problems only if they consider each other as balancing possibilities.